PEMANFAATAN MUSEUM BALANGA SEBAGAI SARANA EDUKASI SEJARAH LOKAL KALIMANTAN TENGAH DALAM MENINGKATKAN KESADARAN BUDAYA MASYARAKAT - Sri Astuti; Muhammad Husni (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to examine the Balanga Museum as a learning resource for the local history of Central Kalimantan. The method used is descriptive qualitative, with data collection techniques through observation, documentation, and literature review, as well as interactive data analysis. The results show that the Balanga Museum houses ethnographic, archaeological, and numismatic collections, such as mandau (a type of sword), lunju (a type of stilt), traditional clothing, balanga (a type of dagger), whale fossils, and rupiah banknotes, representing the history and culture of the Dayak people. These collections serve as contextual learning media that can enhance students' understanding and interest in learning through direct museum experiences. Furthermore, the museum is also utilized as a non-formal learning facility that is both educational and recreational, although optimization through the integration of learning tools is still needed. Thus, the Balanga Museum has the potential to be an effective and contextual source for learning about history.